Sistem Pendukung Keputusan Pengadopsian Anak Menggunakan Metode Analytical Hierarchy Process Dan Metode Perbandingan Eksponensial - Ajeng Dhanty Yoshima; Dwi Remawati; Muhammad Hasbi (STMIK Sinar Nusantara, 2021)
YPAB is an institution that keeps and takes care babies and children who don’t have parents. The babies and the children can be adopted, but the institution has their own regulations for potential adopters who want to adopt children. All this time, adopter who adopted the babies or the children from YPAB institution is done manually which need long time. Therefore, DSS is needed for decide a potential adopter. The purpose of this research is developing a DSS in the process of selecting potential adopters. Meanwhile, the research method uses the Analytical Hierarchy Process (AHP) and the Exponential Comparison Method (MPE) and the System testing uses black-box and validity testing. System testing is used black-box and validity testing by comparing the real YPAB data and the calculation system results. The test results show that the adoption system using the Analytical Hierarchy Process (AHP) method and the Exponential Comparison Method (MPE) has a good performance so that the system is feasible to be implemented in YPAB.